Unraveling Heparan Sulfate Proteoglycan Binding Motif for Cancer Cell Selectivity - Brunetti, Jlenia; Riolo, Giulia; Depau, Lorenzo; Mandarini, Elisabetta; Bernini, Andrea; Karousou, Evgenia; Passi, Alberto; Pini, Alessandro; Bracci, Luisa; Falciani, Chiara (Frontiers in Oncology, 2019)
Membrane heparan sulfate proteoglycans (HSPG) regulate cell proliferation, migration, and differentiation and are therefore considered key players in cancer cell development processes. Here, we used the NT4 peptide to investigate how the sulfation pattern of HSPG on cells drives binding specificity. NT4 is a branched peptide that binds the glycosaminoglycan (GAG) chains of HSPG. It has already been shown to inhibit growth factor-induced migration and invasiveness of cancer cells, implying antagonist binding of HSPG. The binding affinity of NT4 with recombinant HSPG showed that NT4 bound glypican-3 and -4 and, with lower affinity, syndecan-4. NT4 binding to the cancer cell membrane was inversely correlated with sulfatase expression. NT4 binding was higher in cell lines with lower expression of SULF-1 and SULF-2, which confirms the determinant role of sulfate groups for recognition by NT4. Using 8-mer and 9-mer heparan sulfate (HS) oligosaccharides with analog disaccharide composition and different sulfation sites, a possible recognition motif was identified that includes repeated 6-O-sulfates alternating with N- and/or 2-O-sulfates. Molecular modeling provided a fully descriptive picture of binding architecture, showing that sulfate groups on opposite sides of the oligosaccharide can interact with positive residues on two peptide sequences of the branched structure, thus favoring multivalent binding and explaining the high affinity and selectivity of NT4 for highly sulfated GAGs. NT4 and possibly newly selected branched peptides will be essential probes for reconstructing and unraveling binding sites for cancer-involved ligands on GAGs and will pave the way for new cancer detection and treatment options.